DALAM PERSPEKTIF POSTMODERNISME (MELIHAT KASUS PENERAPAN STANDARDISASI LINGKUNGAN) - Anna Yulia Hartati (SPEKTRUM, 2008)
AbstractThe article explores how postmodernism perspective (borrows from Foucault Analyze) explaining environment standardization adjustment as a effort for sustaining capitalist power. That is linked with development jargon which must be done byunder develop country with develop states recipe. Behind that issue the develop countries has prepared environment technology and management so their product could satisfy international environment standardization. Because of thatcompetition, the under develop countries must adopt the standard although they don’t have any resources for applying the technology on their product, the condition is looked as being forced by develop countries for their eternity power with knowledge : environment technology and management system that they have. Beside they could perpetuate their capital, on the other environment matter could be handled by protecting on international environment standardization.Key Words : Postmodernism Perspective, Environment Standardization, Capitalism